Celebrating Africana Motherhood: the Shona Proverb and the Familial and Social Roles of Mothers as First Teachers, Cultural Bearers and Co-Partners - Mazuru, Michael; Nyambi, Oliver (International Journal of Asian Social Science, 2012)
The position and role of women in Shona culture has been largely distorted and misrepresented due to the influence of Western Feminist theoretical paradigm which seeks to define and construct the Shona and, by extension, the Africana women from the standpoint of its rootedness in its own struggles against European patriarchy. This has negatively impacted on the growth and transcendence of both continental and Diasporan Africana women who stand at the mercy of „marauding‟ groups of European women and organisations peddling Western oriented emancipatory ideas. Owing to their ethnocentric grounding in the European conception of reality which masquerades as universal, these ideas cannot hold in a fast globalising world that plays host to a hodgepodge of cultural worldviews and their attendant problems and challenges. It is therefore the concern of this paper to explicate the values and roles of Africana mothers as celebrated in Shona proverbs. The argument is that Shona/Africana women have an influential position as custodians of Shona/Africana cultural values, first teachers and co-partners in the Shona/Africana struggle for well being, survival and transcendence. The Shona/Africana woman is therefore celebrated as the campus of every home and family. She is the cardinal point from which the energy and strength that sustains the home and family ensues.